GENITALIA HYGIENE HEALTH EDUCATION AND TRAINING FOR STUDENTS IN CLASS X AND XI SMA NEGRI 5 SAMARINDA - Nur Rohmah; Rina Tri Agustini; Abira Ivanca Eka Dewi Sitepu; Annisa Delillah Priyanti; Grace Zecharrias Inanda; Resha Rizqy Nabila; Lies Permana (Universitas Widya Gama Mahakam Samarinda, 2023)
Nowadays, there are many infectious and non-communicable diseases that easily infect a person, one of the efforts is to prevent disease infection by implementing good and correct personal hygiene. The reproductive organs must also be maintained in hygiene and health which can be called genitalia hygiene. However, genitalia hygiene is still taboo in Indonesian society so there are no specific guidelines that are taught formally or with standard health standards because it is considered only a hereditary science. In fact, hygiene behavior is very important to do well in preventing negative impacts on the reproductive health of women who are also prospective mothers in the future. The purpose of this study is to explain the influence of